PENGGUNAAN TOKSIN BOTULINUM-A DENGAN PANDUAN ULTRASONOGRAFI SEBAGAI TERAPI SINDROM PIRIFORMIS REKUREN: SERIAL KASUS - Yusak Mangara Tua Siahaan (PERDOSNI, 2020)
Piriformis syndrome (PS) is a clinical syndrome with complaints of buttock pain that radiates to the unilateral side leg caused by sciatic nerve entrapment of piriformis muscle. Several therapy modalities of PS are oral, physical, intervention, and surgical therapy. Intramuscular injection therapy is an intervention therapy for patients who experience severe pain or have failed oral therapy and/or physical therapy. It generally involves the use of local anesthetics, corticosteroids or the botulinum toxin A. This study represents five cases of short-period recurrent PS in 4 females and 1 male with age variations from 32 to 43 years-old. All cases complained classic symptoms with sub-acute to chronic onset and previously had a conservative-interventional therapy. Long-term improvement (>9 months) was experienced after intramuscular botulinum-toxin-A injection with ultrasound-guided. Keywords: Botulinum toxin, injection therapy, piriformis syndrome.